Menghargai Perbedaan: Fondasi Toleransi Beragama dalam Perspektif Islam Berdasarkan Al-Qur'an - Farisa Rahmadani; Hadiska Nofriawan; Dzulfikar Arif (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study examines the concept of responsibility in maintaining trust (amanah) through the perspectives of Quranic verses and hadiths and explores its relevance to contemporary social, family, and religious issues. In the face of increasingly complex social challenges, the values of responsibility and trustworthiness remain essential ethical foundations for fostering harmonious and accountable communities. This study employed a qualitative approach using a literature review method by analyzing Quranic verses, hadiths, and relevant scholarly references. The analysis focuses on three main themes: parental responsibility in the family based on QS. At-Tahrim verse 6 integrated with the concept of life balance; leadership responsibility in QS. Al-An'am verse 70 associated with anti-corruption leadership; and religious responsibility in QS. An-Nisa verse 36 examined in relation to the phenomenon of Islamophobia. The findings reveal that the Islamic concept of amanah provides a comprehensive normative framework for individual, family, social, and collective responsibilities. The selected hadiths reinforce Quranic teachings by offering practical guidance for ethical behavior and responsible leadership. Furthermore, integrating these teachings with contemporary issues demonstrates that Islamic values remain relevant in addressing modern societal challenges, including governance, family resilience, and interreligious relations. This study concludes that internalizing the values of trust, responsibility, tolerance, and justice can strengthen social harmony, promote ethical leadership, and support peaceful coexistence in Indonesia and other multicultural Muslim societies.